2007
DOI: 10.1111/j.1747-0803.2007.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Pulmonary Arterial Hypertension with Inhaled Epoprostenol in an Infant with Congenital Heart Disease

Abstract: Epoprostenol is a potent arterial vasodilator, and its administration by inhalation localizes its effects to the pulmonary circulation. In this case report, we describe a 3-month-old male patient with significant refractory pulmonary hypertension after pulmonary artery banding and placement of a Blalock-Taussig shunt. This patient continued to have significant hypoxic episodes despite maximal therapy with sedation, alkalinization, sildenafil, and inhaled nitric oxide. After the addition of inhaled epoprostenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Another case report showed a synergistic effect of inhaled epoprostenol and iNO in the treatment of refractory PAH in a 3-month-old male patient with D-TGA and ventricular septal defect after pulmonary artery banding and placement of a Blalock-Taussig shunt. 55 In a prospective interventional pilot study, Carroll and colleagues 56 examined the physiologic effects of inhaled epoprostenol (15-minute course, intraoperatively and postrepair) in 6 children with PAH-CHD. They found that the agent significantly reduced mPAP and improved oxygenation.…”
Section: Prostacyclin Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case report showed a synergistic effect of inhaled epoprostenol and iNO in the treatment of refractory PAH in a 3-month-old male patient with D-TGA and ventricular septal defect after pulmonary artery banding and placement of a Blalock-Taussig shunt. 55 In a prospective interventional pilot study, Carroll and colleagues 56 examined the physiologic effects of inhaled epoprostenol (15-minute course, intraoperatively and postrepair) in 6 children with PAH-CHD. They found that the agent significantly reduced mPAP and improved oxygenation.…”
Section: Prostacyclin Analogsmentioning
confidence: 99%
“…In 1995, Zwissler 54 described the successful intra‐ and postoperative use of aerosolized epoprostenol, without causing systemic hypotension or deterioration of gas exchange, in a newborn with total anomalous pulmonary venous connection and severe PAH. Another case report showed a synergistic effect of inhaled epoprostenol and iNO in the treatment of refractory PAH in a 3‐month‐old male patient with D‐TGA and ventricular septal defect after pulmonary artery banding and placement of a Blalock‐Taussig shunt 55 . In a prospective interventional pilot study, Carroll and colleagues 56 examined the physiologic effects of inhaled epoprostenol (15‐minute course, intraoperatively and postrepair) in 6 children with PAH‐CHD.…”
Section: Prostacyclin Analogsmentioning
confidence: 99%
“…Golzand et al 9 reported on the use of epoprostenol in an infant with PPHN refractory to iNO with good response, leading to discontinuation of both PH‐specific agents. Finally, Kovach et al 10 reported on the use of inhaled epoprostenol in an infant with CHD refractory to iNO that resulted in dramatic improvements in ventilation and oxygenation, leading to discontinuation of both PH‐specific agents.…”
Section: Introductionmentioning
confidence: 99%
“…Dextro-transposition of the great arteries and intact ventricular septum associated with persistent pulmonary hypertension is uncommon and associated with poor outcomes 1 . Several therapeutic interventions have been described to improve systemic oxygen delivery and reduce oxygen consumption including balloon atrial septostomy, prostaglandin infusion to maintain ductal patency, inotropic support, 2 inhaled nitric oxide, 3 , 4 epoprostenol, 5 bosentan 6 , and extracorporeal membrane oxygenation 4 7 , 8 We present three patients with dextro-transposition of the great arteries, intact ventricular septum, and refractory persistent pulmonary hypertension of the newborn supported with extracorporeal membrane oxygenation preoperatively, separated from bypass following their arterial switch operation and survived to discharge with favourable long-term follow-up.…”
mentioning
confidence: 99%